POLITIK ALIENASI BIROKRASI - Pratama, Dedi Zulkarnain (Faculty of Social and Political Science Universitas Brawijaya, 2017)
This paper discusses about political process of alienation by bureaucrat in Central Lombok region. Political policy of alienation is conducted by government in purpose to punish several bureaucrats that politically oppose in local election. Alienation policy is political punishment towards bureaucrats in purpose to cut off surely their career. If it is not, the bureaucrat will be non-job. Because of that, the political policy of alienation is very frightening for local bureaucrats who dissent with head of local government.